Determinant factors related to variation in butterfly velocity - Martins-Silva, A.; Alves, F. (coachesinfo.com, 2000)
In this paper, which is the result of several studies, the purpose was to: (i) describe the intra cycle CMbody velocity behaviour; (ii) evaluate the determinant factors related to the variation in horizontal velocity of the body centre of mass in butterfly, considering different technical simulations. The results led to the conclusion, that the major determinant factors related to the CMbody velocity variation are: (i) those directly related to the high hand horizontal, vertical and lateral velocity during the last phases of the arm stroke (upsweep and exit); (ii) those directly related to the low of hand velocity in all directional components during the most lateral phases of the arm stroke (insweep).